Leveraging corporate tax incentives to attract FDI: design and implementation considerations - Hania Kronfol (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2020)
Countries are increasingly relying on corporate tax incentives to attract FDI. However, governments often overestimate the role of these instruments in swaying investors, translating to lost tax revenue, market distortions, and other unintended consequences. This Perspective provides good practice guidelines for policymakers to adopt incentives in a strategic, cost-effective manner.
Keywords: 330